Implementasi dan Analisi Image Scalling Menggunakan Bilinier Interpolation pada Citra Kendaraan - Fahmi Ramadhan (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Digital image processing is an essential area in computer science, particularly in manipulating and transforming images for analysis and visualization purposes. One of the fundamental techniques is image scaling, which involves enlarging or reducing the dimensions of an imageThe tests indicate that extreme downscaling leads to a significant decrease in image quality, reflected by lower PSNR and higher MSE. In contrast, moderate upscaling tends to preserve more visual quality, although it cannot enhance image details beyond the original resolution. In conclusion, the bilinear interpolation method can be effectively applied for image scaling in light to moderate scenarios. The evaluation using PSNR and MSE provides a clear quantitative insight into image degradation caused by scaling. This application can serve as a foundation for further development in image processing systems, such as object detection, vehicle classification, or visual surveillance systems.